THE ROLE OF GUT MICROBIOTA IN THE PATHOGENESIS OF DEPRESSION - CURRENT STATE OF KNOWLEDGE - Agnieszka Zaleszczyk; Katarzyna Oświeczyńska; Agnieszka Kasprzak; Patrycja Jędrzejewska-Rzezak (International Journal of Innovative Technologies in Social Science, 2025)
In recent years, there has been growing interest in the role of the gut microbiome in modulating brain function and its potential impact on mental disorders, including depression. The gut-brain axis, a complex communication network between the gastrointestinal tract and the central nervous system, is crucial for comprehending the relationship between gut microbiota and mental health. Communication along this pathway takes place through various pathways: neuronal, hormonal, and immunological. Multiple preclinical and clinical investigations demonstrate that alterations in the composition and diversity of gut microbiota can influence neuroinflammatory mechanisms, neurotransmitter metabolism, and hypothalamic-pituitary-adrenal (HPA) axis function, potentially facilitating the emergence of depressive symptoms. This article aims to examine contemporary findings about the mechanisms by which the gut microbiome affects mood and to evaluate potential treatment strategies, including psychobiotics, dietary modifications, and fecal microbiota transplantation. Comprehending the function of the microbiome in the etiology of depression could provide novel avenues for the diagnosis and treatment of affective disorders. Although the current state of knowledge does not yet allow the formulation of concrete conclusions and diagnostic and therapeutic recommendations, it certainly encourages further research.